Develop a mathematical model of the grading scale to make Examinations are an effective method (Journal of the College of Basic Education, 2023)
A mathematical model of the grading scale was developed to make the exam as if it were perfect, and it leads to a normal distribution of students' grades similar to the distribution in the Gauss curve, and the research also shows how the quality of the subject scale can be tested. The research contained the results of a practical application of the proposed model for students of Applied Sciences - University of Technology in the subject (Life Sciences).The research also used the correction table in the process of detecting the difficulties that students face during the study, in order to discover the causes of the difficulties and seek to address them, which gives importance to the semester exams in the development of the educational process.The research gives a quantitative measure of the students' academic achievement level, which is an independent indicator of the students' grades and is useful in evaluating the educational process's returns abstractly and objectively.